Impact of sectoral determinations in previously unregulated sectors: a case study of domestic work in Grahamstown - Nxokweni, Saphokazi (Rhodes University, Faculty of Humanities, Department of Sociology, 2016)
Domestic labour is widely recognized as one of the most vulnerable labour sectors, both nationally and internationally. In South Africa, sectoral determination 7 was specifically developed to protect domestic workers' rights and provide them with the means to negotiate with and hold employers to account. However, research over the past years has demonstrated that, while some areas of domestic labour have improved, many workers are still locked in exploitative labour relationships. This research shows that it may seem as if there are significant changes in this sector since the introduction of the sectoral determination, but paternalistic orientations, one-of-the-family myths, and food distribution suggest otherwise. The research concluded that continuities of exploitative and discriminatory practices are still prominent in the employment relationship when viewed through the lens of paternalistic care, food distribution, and the 'one-of-the-family' myth.
Keywords: Uncatalogued